2019
DOI: 10.1200/cci.19.00031
|View full text |Cite
|
Sign up to set email alerts
|

Text Mining in Electronic Medical Records Enables Quick and Efficient Identification of Pregnancy Cases Occurring After Breast Cancer

Abstract: PURPOSE To apply text mining (TM) technology on electronic medical records (EMRs) of patients with breast cancer (BC) to retrieve the occurrence of a pregnancy after BC diagnosis and compare its performance to manual curation. MATERIALS AND METHODS The training cohort (Cohort A) comprised 344 patients with BC age ≤ 40 years old treated at Institut Curie between 2005 and 2007. Manual curation consisted in manually reviewing each EMR to retrieve pregnancies. TM consisted of first applying a keyword filter (“acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Ensuring sufficient preparation of such data is particularly important, as research has found that the application of text mining to medical records can expedite information extraction and enhance health-related outcomes. For example, Labrosse et al (57) extracted information from 344 patients' electronic health records using both manual tracking and text mining techniques to identify the rare event of pregnancy following breast cancer (incidence rate of 0.01 pregnancy per person-year after breast cancer diagnosis). The authors found that text mining was more efficient than manual tracking (13 vs. 244 min, respectively) in identifying rare events in electronic health records.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring sufficient preparation of such data is particularly important, as research has found that the application of text mining to medical records can expedite information extraction and enhance health-related outcomes. For example, Labrosse et al (57) extracted information from 344 patients' electronic health records using both manual tracking and text mining techniques to identify the rare event of pregnancy following breast cancer (incidence rate of 0.01 pregnancy per person-year after breast cancer diagnosis). The authors found that text mining was more efficient than manual tracking (13 vs. 244 min, respectively) in identifying rare events in electronic health records.…”
Section: Discussionmentioning
confidence: 99%
“…The number of encounters or ICD-9/10 codes have been found to be a useful component of algorithms used to identify patient populations, but it is widely recognized that more than one type of data are necessary to reliably identify a clinical population [10]. Further, the use of one or two EMR-derived data types is generally limited in classification ability, with better ability to identify pregnancy or birth outcomes achieved when more data types or complex data derivation techniques, such as text mining, are applied [23,24]. Along these lines, we did detect a statistically significant difference in the proportion of women with an EMR HDP diagnosis between women with versus without at least one or two hypertensive EMR BP readings.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy cases were identified by text mining technology as previously described [ 35 ]. Briefly, the text mining approach consisted in applying a keyword filter (“accouch *” or “enceinte”, French terms for “deliver *” and “pregnant”, respectively) on the medical electronic records of patients to select a subset of files.…”
Section: Methodsmentioning
confidence: 99%